2015
DOI: 10.1017/s1368980015000993
|View full text |Cite
|
Sign up to set email alerts
|

Weight expectations, motivations for weight change and perceived factors influencing weight management in young Australian women: a cross-sectional study

Abstract: Objective: To examine young Australian women's weight expectations, motivations for weight change and perceived factors influencing weight management, and to determine if these factors differ by age, BMI, marital status, education or income. Design: Cross-sectional study. An online survey captured respondents' weight, height, ideal weight, main reasons for wanting to change their weight and challenges to managing their weight. Setting: Online survey in Australia. Subjects: Six hundred and twenty women aged 18-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 52 publications
(108 reference statements)
5
38
0
1
Order By: Relevance
“…Thirty‐four studies articles were included. The majority of studies (15/34) were conducted in the USA , followed by Australia (8/34) , England (4/34) and one in Scotland (1/34) , Canada (1/34) , Sweden (1/34) , The Netherlands (1/34) , Bahrain (1/34) , Germany (1/34) and Belgium (1/34) . The studies included were all published after 2005 and distributed throughout the next 10 years from 2006 to 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐four studies articles were included. The majority of studies (15/34) were conducted in the USA , followed by Australia (8/34) , England (4/34) and one in Scotland (1/34) , Canada (1/34) , Sweden (1/34) , The Netherlands (1/34) , Bahrain (1/34) , Germany (1/34) and Belgium (1/34) . The studies included were all published after 2005 and distributed throughout the next 10 years from 2006 to 2015.…”
Section: Resultsmentioning
confidence: 99%
“…A subset of data from a survey of young women 15 was used to determine their interest in an e-health weight loss program and their preferred means of program delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Program components were further targeted to young women by considering their specific motivations for wanting to control their weight (i.e., ''feel better about themselves,'' ''increase self-confidence,'' ''improve health''), 15 as well as primary barriers to weight management (i.e., time, motivation, cost). 15 Branding and graphic design throughout the program materials also reflected young women (e.g., images of young women). Specific details of the program components and how they align with cognitive behavioral therapy strategies are described in Table 3.…”
Section: Aim 2: Program Descriptionmentioning
confidence: 99%
“…Positive expectations for weight loss are often improved health, self-confidence, and appearance. 21,22 One study revealed that participants lost more weight when they reported higher positive outcome expectancy scores. 16 However, individuals in weight loss programs often have unrealistic expectations or are unaware of the diverse behavior changes needed to meet their goals, resulting in frustration, self-deprecation, and quitting.…”
Section: Expectancies In Treatment Outcomesmentioning
confidence: 99%